2022
DOI: 10.3389/fped.2022.925951
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oxygenation and Metabolism After Hypoxia-Ischemia

Abstract: Perinatal hypoxia-ischemia (HI) is still a significant contributor to mortality and adverse neurodevelopmental outcomes in term and preterm infants. HI brain injury evolves over hours to days, and involves complex interactions between the endogenous protective and pathological processes. Understanding the timing of evolution of injury is vital to guide treatment. Post-HI recovery is associated with a typical neurophysiological profile, with stereotypic changes in cerebral perfusion and oxygenation. After the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…The decrease in CMRO 2 occurred in the first hours after the HI insult, and during the same time period, CBF was equal to control animals ( 45 ). These findings are in accordance with previously postulated hypothesis of metabolic suppression during the latent phase of injury ( 5 , 46 ). However, no such change in cerebral metabolism was detected in this study as oxygen tension and rSO 2 returned to baseline levels after the HI insult.…”
Section: Discussionsupporting
confidence: 93%
“…The decrease in CMRO 2 occurred in the first hours after the HI insult, and during the same time period, CBF was equal to control animals ( 45 ). These findings are in accordance with previously postulated hypothesis of metabolic suppression during the latent phase of injury ( 5 , 46 ). However, no such change in cerebral metabolism was detected in this study as oxygen tension and rSO 2 returned to baseline levels after the HI insult.…”
Section: Discussionsupporting
confidence: 93%
“…The current single-cell transcriptomic sequencing also found that the two have similar phenotypes ( 89 ). Activated microglia/macrophages have been found to produce a variety of mediators, including iNOS ( 90 ), inflammatory cytokines (such as TNF-α, IL-1β, TGF-β, IL-10) ( 86 ), nerve growth and trophic factors (such as IGF-1, bFGF, PDGF, BDNF) ( 91 ).…”
Section: Mechanisms Of Microglia/macrophages In Ismentioning
confidence: 99%
“…Its onset and progression depend on the extent and severity of the injury. The more severe the injury, the earlier the onset of the secondary phase [29]. Although the exact mechanism of the secondary energy failure remains unknown, necrosis and reperfusion injury in the neonatal brain following primary energy failure are considered key factors.…”
Section: Pathophysiology and Neural Cell Deathmentioning
confidence: 99%